High-filling modified calcium carbonate powder capable of improving ABS performance and preparation method of high-filling modified calcium carbonate powder

By using high-filled modified calcium carbonate powder in ABS plastics, combined with additives such as stearic acid, long-chain silane coupling agents, an organic single-molecular layer and a lubricating layer are formed, which solves the problem of limited filling amount of CaCO3, and improves ABS performance and reduces costs.

CN119684680APending Publication Date: 2025-03-25SHANDONG JINSHENG NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411858026.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the prior art, the amount of CaCO3 in ABS plastics is limited, resulting in limited impact performance and hardness improvement, while high filling volume will lead to performance deterioration and cost increase.

Method used

Using high-filled modified calcium carbonate powder, the organic monolayer and lubricating layer are formed by adding components such as stearic acid, long-chain silane coupling agent, aluminate coupling agent, titanate coupling agent and modifier, to improve the compatibility and dispersion of CaCO3 and ABS.

Benefits of technology

It achieves a significant reduction in costs while maintaining ABS performance and improves the impact performance, hardness and surface gloss of ABS.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684680A_ABST
    Figure CN119684680A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of calcium carbonate powder modification, and discloses high-filling modified calcium carbonate powder for improving ABS performance and a preparation method thereof, the high-filling modified calcium carbonate powder comprises the following components by mass: 100 parts of calcium carbonate powder, 0.5-0.7 part of stearic acid, 0.5-0.8 part of a long-chain silane coupling agent, 0.6-1.0 part of an aluminate coupling agent, 0.3-0.5 part of a titanate coupling agent, 1.0-1.3 parts of a modifier, and 0.3-0.5 part of a dispersant; the modified calcium carbonate powder has the characteristics of being good in dispersity, high in whiteness, high in activation degree, low in oil absorption value, simple and convenient to prepare and the like, has the advantages of being large in filling amount, high in gloss, capable of improving the tensile strength, the impact strength, the bending strength, the thermal deformation temperature and the flowability of the ABS plastic and the like when being used for filling the ABS plastic, and is rare special modified calcium carbonate powder for filling the ABS plastic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of calcium carbonate powder modification, in particular to a highly filled modified calcium carbonate powder for improving ABS performance, and also to a preparation method of the modified calcium carbonate powder. Background Art

[0002] ABS plastics are widely used in the fields of automobiles, home appliances, office equipment, communications, etc. due to their excellent mechanical properties, good processing properties, chemical resistance, good surface gloss and other excellent properties, becoming one of the most commonly used general engineering plastics. 3 (Calcium carbonate) has the characteristics of wide source, low price, high whiteness and non-toxicity, making it one of the most widely used fillers in the field of plastic material modification.

[0003] Currently used in ABS plastic modification, CaCO 3 , all using ultrafine CaCO 3 or nano-CaCO 3 When using ultrafine CaCO 3 or nano-CaCO 3 When filling ABS plastic, due to CaCO 3 The presence of CaCO will produce a stress concentration effect, which can easily cause micro-cracks in the surrounding resin and absorb a certain amount of deformation work. 3 The presence of CaCO also hinders and blunts the crack propagation of the matrix resin, and eventually stops the crack from developing into destructive cracking. 3 As inorganic rigid particles, it has the advantages of improving the impact performance and hardness of ABS plastic, but CaCO 3 The filling amount in ABS plastic is extremely limited, which is only less than 10% of the mass of ABS plastic. Studies have shown that when CaCO 3 When the filling amount is large, the B phase in the ABS plastic terpolymer, that is, the rubber phase butadiene and the inorganic rigid particle CaCO 3 The interaction reduces the impact energy and makes the dispersion worse (see Shen Jirui, Shen Zhigang, Chen Jianfeng, etc. for details. ABS plastic / modified nano-CaCO 3 Microstructure and mechanical properties of composite materials (J). Polymer Materials Science and Engineering, 2004, 20(3): 126-129); too low CaCO 3 The amount of addition will become a key factor restricting the cost of ABS plastic materials. Therefore, it is necessary to further modify the calcium carbonate powder. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a highly filled modified calcium carbonate powder for improving the performance of ABS, so as to reduce the cost while improving or maintaining the performance of ABS plastic.

[0005] In order to solve the above technical problems, the technical solution of the present invention is: a highly filled modified calcium carbonate powder for improving the performance of ABS, comprising the following components in proportion by mass:

[0006] 100 parts of calcium carbonate powder, 0.5-0.7 parts of stearic acid, 0.5-0.8 parts of long-chain silane coupling agent, 0.6-1.0 parts of aluminate coupling agent, 0.3-0.5 parts of titanate coupling agent, 1.0-1.3 parts of modifier, and 0.3-0.5 parts of dispersant.

[0007] As a preferred technical solution, the particle size of the calcium carbonate powder tested by Malvern particle size tester is D 50 ≦1.54μm, D 97 Heavy calcium carbonate powder ≦9.38μm.

[0008] As a preferred technical solution, the raw material ore for preparing the heavy calcium carbonate powder is large calcite or small calcite, which is obtained by grinding with a vertical mill and then classifying;

[0009] When the ore is ground, 1 to 1.5‰ of grinding aid needs to be added;

[0010] The grinding aid is one of sodium dodecyl sulfonate, sodium hexametaphosphate and sodium polystyrene sulfonate;

[0011] The preparation of the heavy calcium carbonate powder comprises the following steps:

[0012] SP A1 , washing, using tap water or clean water to wash the ore to remove the sand and humus adhering to the surface of the ore;

[0013] SP A2 3. Sorting: sorting the cleaned ore to remove the miscellaneous colored ore that affects the white hue;

[0014] SP A3 First, crushing the ore into small pieces by using a jaw crusher;

[0015] SP A4 Secondary crushing: jaw crusher is used to crush small pieces of ore into crushed ore with a maximum size not exceeding 30mm;

[0016] SP A5, dilution, taking distilled water of 15 to 25 times the mass of the grinding aid, adding the distilled water to the grinding aid to dilute it, and then pouring it into a liquid storage tank equipped with a metering pump, the liquid inlet of the metering pump is connected to the lower part of the liquid storage tank and close to the bottom thereof, the liquid outlet of the metering pump is connected to an infusion tube, the infusion tube is connected to a nozzle rod, and the nozzle rod is equipped with a nozzle;

[0017] SP A6 , spray, SP A4 The crushed ore obtained in the step is metered and transported to the vertical mill by a vibrating screen. During the transportation of the crushed ore, the diluted grinding aid is sprayed onto the surface of the crushed ore by a metering pump according to a set mass ratio with the crushed ore;

[0018] SP A7 , grinding, adjusting the process parameters of the vertical mill for grinding, the vertical mill outputs the calcium carbonate powder mixed with large particles of calcium carbonate into the classifier for classification, the large particles of calcium carbonate are returned to the vertical mill after classification to continue to participate in grinding, the calcium carbonate powder enters the collector for classification, and the collector parameters are adjusted to separate the coarse powder and the fine powder, and the particle size of the fine powder is D 50 ≦1.54μm, D 97 Calcium carbonate powder ≦9.38μm.

[0019] As a preferred technical solution, the long-chain silane coupling agent is one of alkoxy-terminated polydimethylsiloxane, 1,3-bis[3-(1-methoxy-2-hydroxypropoxy)propyl]-terminated polysiloxane, and octadecyltrimethoxysilane;

[0020] The structural formula of the alkoxy-terminated polydimethylsiloxane is:

[0021]

[0022] Where a = 0 or 1, R 1 , R 2 is methyl or ethyl, and n is 20 to 300;

[0023] The structural formula of the 1,3-bis[3-(1-methoxy-2-hydroxypropoxy)propyl]-terminated polysiloxane is:

[0024]

[0025] n is 10 to 100;

[0026] The structural formula of the octadecyltrimethoxysilane is,

[0027]

[0028] As a preferred technical solution, the aluminate coupling agent is one of isopropyl distearoyloxy aluminate, phosphate acyloxy isooctyl aluminate, and anti-settling aluminate.

[0029] As a preferred technical solution, the titanate coupling agent is one of isopropyl tri(dioctyl phosphate) titanate and bis(dioctyl pyrophosphate) ethylene titanate.

[0030] As a preferred technical solution, the modifier is ethyl levulinate glycidyl ketal, C 21 One of the diglycidyl esters of dicarboxylic acids;

[0031] The structural formula of the ethyl levulinate glycidyl ketal is:

[0032]

[0033] The C 21 The structural formula of diglycidyl dicarboxylate is:

[0034]

[0035] As a preferred technical solution, the dispersant is a hyperdispersant, including one of a pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type hyperdispersant, a styrene-butyl acrylate-2-acrylamide-2-methylpropane sulfonic acid ternary copolymer, and a sulfonate type hyperdispersant;

[0036] The structural formula of the pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type hyperdispersant is

[0037] Where n:m:f=7:36:1;

[0038] The structural formula of the 2-acrylamide-2-methylpropanesulfonic acid-styrene-butyl acrylate terpolymer is:

[0039]

[0040] Where x:y:z=1:1:0.5;

[0041] The structural formula of the sulfonate type hyperdispersant is:

[0042]

[0043] Among them, a:b:c=1:0.5:1, and n is 8 to 10.

[0044] The present invention also relates to a method for preparing a highly filled modified calcium carbonate powder for improving ABS performance, which is prepared by combining an auxiliary agent metering system group and a zero-gravity mixing unit.

[0045] The additive metering system group includes five metering pump metering systems and one loss-in-weight scale metering system;

[0046] The zero-gravity mixer unit includes a zero-gravity mixer for modification and a zero-gravity mixer for cooling;

[0047] The metering pump metering system comprises a liquid storage tank with a heating function, a metering pump connected to the liquid storage tank, a liquid infusion tube connected to the metering pump, a nozzle rod installed at the other end of the liquid infusion tube, and a nozzle installed at the end of the nozzle rod;

[0048] The loss-in-weight weighing system comprises a barrel, a hopper is installed above the barrel, a blanking barrel is installed at the discharge end of the barrel, a screw is installed inside the barrel, one end of the screw extends to the outside of the feed end of the barrel, and the end of the screw extending to the outside of the barrel is connected to a power device;

[0049] The modified zero-gravity mixer comprises a shell, a chamber is arranged in the shell, the lower part of the chamber is in an "ω"-shaped structure, and the upper part is in a rectangular parallelepiped structure, two transmission shafts are installed in parallel in the "ω"-shaped structure of the chamber, one end of each transmission shaft is rotatably installed on the shell, and is limited to the outside of the shell, and the other end extends to the outside of the shell and is connected to a power device through a chain drive, and stirring tooth groups are evenly installed on each of the transmission shafts, and the stirring tooth groups are respectively composed of four groups of mutually perpendicular stirring teeth, and the stirring teeth are arranged at an angle of 45° with the corresponding transmission shafts, and the inner wall of the chamber is located at each Flying knives are respectively installed under the transmission shaft; the shell is provided with a hollow interlayer, which is connected to an external heat-conducting oil heating system; discharge ports are respectively arranged directly below the "ω" structure of the chamber, and a discharging motor of a weightless mixer for modification is installed on the discharge port; a raw material addition port is opened in the middle of the top of the weightless mixer for modification, an auxiliary agent addition port is opened on one side of the raw material addition port, the nozzle rod of the metering pump metering system and the blanking barrel of the loss-in-weight scale metering system are both installed on the auxiliary agent addition port; the hollow interlayer of the cooling weightless mixer is connected to a water cooling system.

[0050] As a preferred technical solution, a method for preparing a highly filled modified calcium carbonate powder for improving ABS performance comprises the following steps:

[0051] SP B1, heating the modified weightless mixer, setting the heating temperature to 85-95° C., and maintaining the temperature for 30 minutes after the heating reaches the set temperature; passing cooling water through the cooling weightless mixer;

[0052] SP B2 , placing stearic acid into the liquid storage tank of the first metering pump metering system and heating it to melt, and the heating temperature is controlled at 75-85°C; placing the long-chain silane coupling agent into the liquid storage tank of the second metering pump metering system and heating it, and the heating temperature is controlled at 65-75°C; placing the aluminate coupling agent into the liquid storage tank of the third metering pump metering system and heating it to melt, and the heating temperature is controlled at 85-95°C; placing the titanate coupling agent into the liquid storage tank of the fourth metering pump metering system and heating it, and the heating temperature is controlled at 50-60°C; placing the modifier into the liquid storage tank of the fifth metering pump metering system and heating it, and the heating temperature is controlled at 60-70°C;

[0053] SP B3 , placing the dispersant into the hopper of the loss-in-weight measuring system;

[0054] SP B4 , start the weightless mixer for modification, and mix the A7 The prepared calcium carbonate powder is metered into the weightless mixer for modification, the amount of calcium carbonate powder added shall not exceed 2 / 3 of the volume of the weightless mixer for modification, and the speed of the weightless mixer for modification is controlled at 50-70 rad / min;

[0055] SP B5 , start the power device of the loss-in-weight weighing system, measure the dispersant in the hopper according to the mass ratio matching the mass ratio of calcium carbonate added to the modified zero-gravity mixer and evenly add it into the modified zero-gravity mixer, and control the adding time to 60 to 75 seconds;

[0056] SP B6, when the temperature of the calcium carbonate powder in the modified zero-gravity mixer reaches 85°C, start the metering pump on the metering pump metering system where the stearic acid is placed, and spray the heated molten stearic acid evenly onto the calcium carbonate powder in the modified zero-gravity mixer according to the ratio, and the spraying time is controlled to be 30 to 45 seconds. 1 to 2 minutes after the spraying is completed, start the metering pump on the metering pump metering system where the long-chain silane coupling agent is placed, and spray the heated long-chain silane coupling agent evenly onto the calcium carbonate powder in the modified zero-gravity mixer according to the ratio, and the spraying time is controlled to be 45 to 60 seconds. 1 to 2 minutes after the spraying is completed, the metering pump on the metering pump metering system in which the aluminate coupling agent is placed is started again, and the molten aluminate coupling agent is sprayed evenly onto the calcium carbonate powder in the modified weightless mixer according to the proportion, and the spraying time is controlled to be 45 to 60 seconds. 1 to 2 minutes after the spraying is completed, the metering pump on the metering pump metering system in which the titanate coupling agent is placed is started again, and the heated titanate coupling agent is sprayed evenly onto the calcium carbonate powder in the modified weightless mixer according to the proportion, and the spraying time is controlled to be 30 to 45 seconds. After the spraying is completed, stirring and mixing is performed for 15 to 20 minutes;

[0057] SP B7 , start the metering pump on the metering pump metering system where the modifier is placed, spray the heated modifier evenly onto the calcium carbonate powder in the weightless mixer for modification according to the proportion, control the spraying time to 30 to 45 seconds, and continue stirring and mixing for 3 to 5 minutes;

[0058] SP B8 , start the discharging motor of the weightless mixer for modification, put the mixed materials into the weightless mixer for cooling for stirring and cooling, and control the stirring speed to 50-70 rad / min;

[0059] SP B9 After the material is cooled to room temperature, the discharging motor of the cooling zero-gravity mixer installed at the bottom of the cooling zero-gravity mixer is turned on to discharge the material and package it into a finished product.

[0060] Due to the adoption of the above technical solution, the present invention has the following beneficial effects:

[0061] ① The preparation method of the present invention is simple and has low labor intensity, and the prepared modified calcium carbonate powder has good dispersibility, high activation degree and low oil absorption value;

[0062] ② The stearic acid and the aluminate coupling agent added in the present invention can form an organic monolayer on the surface of the calcium carbonate powder according to the monolayer theory. This organic monolayer avoids the interaction between calcium carbonate and B-phase butadiene in ABS, thereby reducing the risk of performance degradation caused by the interaction between calcium carbonate and B-phase butadiene in ABS when the filling is high;

[0063] ③ The long-chain alkyl group in the stearic acid is a lipophilic group, and the carboxyl group (-COOH) group contained therein is a hydrophilic group, which can produce hydrogen bonds with the hydroxyl group (-OH) on the surface of the calcium carbonate powder. When conditions are met, the carboxyl group (-COOH) can undergo an esterification reaction with the hydroxyl group (-OH) on the surface of the calcium carbonate powder to form an ester group (-COO); the long-chain silane coupling agent contains an alkoxy group (-OR) and / or a hydroxyl group (-OH), and the aluminate coupling agent and the titanate coupling agent contain an alkoxy group (-OR) and other active groups, wherein the alkoxy group (-OR) in the CaCO 3 Hydrolysis under the action of bound water generates hydroxyl groups (-OH), which react with hydroxyl groups (-OH) on the surface of calcium carbonate powder to form a strong bond;

[0064] ④ In the present invention, the bonding function of the long-chain siloxane coupling agent and the low surface energy of siloxane, especially polysiloxane, can efficiently migrate to the ABS surface to form a lubricating layer rich in polysiloxane. The film-forming function of the aluminate, the grafting / cross-linking function of the titanate coupling agent, and the titanate coupling agent can dramatically change the surface energy due to the large number of carbon atoms, thereby greatly reducing the viscosity of the system. The long-chain siloxane coupling agent, the aluminate coupling agent, and the titanate coupling agent complement each other, thereby generating coupling superposition synergy (fluidity, mechanical properties, surface gloss, etc.);

[0065] ⑤ The pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate terpolymer type super dispersant, styrene-butyl acrylate-2-acrylamide-2-methylpropane sulfonic acid terpolymer or sulfonate type super dispersant used as the dispersant of the present invention forms an adsorption layer around the particles, which is not easy to desorb, and the solvated chain forms a coating layer on the surface of the particles, and the dispersing effect of the grinding aid makes the calcium carbonate powder obtain good dispersibility;

[0066] ⑥ The stearic acid, the long-chain silane coupling agent, the aluminate coupling agent, and the titanate coupling agent of the present invention are all long-chain structure compounds, which not only have good compatibility with polymer materials, but also have the ability to be entangled with polymer chains and the ability of the stearic acid, the long-chain silane coupling agent, the aluminate coupling agent, and the titanate coupling agent to be entangled with each other, thereby improving the application performance of the composite modified calcium carbonate;

[0067] ⑦ The calcium carbonate powder as the rigid particles in the present invention has the ability to improve the bending strength of the polymer material;

[0068] ⑧ The modifiers described in the present invention are all long-chain epoxy structure modifiers, and their long-chain structures not only have the ability to intertwine with the stearic acid, the long-chain silane coupling agent, the aluminate coupling agent, the titanate coupling agent, and the ABS plastic molecular chain, but also contain highly active epoxy groups. It has the ability to open the ring and break the chain of B-phase butadiene during the processing of the ABS plastic, which reduces the risk of degradation during the processing of the ABS plastic, thereby extending the molecular chain structure of the ABS plastic and improving the performance of the modified calcium carbonate powder filled ABS plastic;

[0069] ⑨ The stearic acid, the long-chain silane coupling agent, the aluminate coupling agent, the titanate coupling agent and the modifier are used in combination with calcium carbonate to improve the surface gloss of the filling material. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] The following drawings are only intended to illustrate and explain the present invention, and are not intended to limit the scope of the present invention.

[0071] in:

[0072] Figure 1 It is a simplified diagram of the main viewing direction of the modified device used in the embodiment of the present invention;

[0073] Figure 2 It is a simplified diagram of the top view of the modification device used in the embodiment of the present invention;

[0074] Figure 3 This is a schematic diagram of the internal structure of a weightless mixer for modification according to an embodiment of the present invention;

[0075] Figure 4 It is a simplified diagram of the structure of the liquid storage tank according to an embodiment of the present invention;

[0076] Figure 5 2 is a schematic diagram of the combination of the nozzle rod and the nozzle according to an embodiment of the present invention;

[0077] Figure 6 is a schematic end view of a nozzle according to an embodiment of the present invention;

[0078] Figure 7 This is a trend diagram showing the effect of the amount of modified calcium carbonate used in Example 1 of the present invention and Comparative Example 2 on the performance of filled ABS;

[0079] Figure 8 This is another trend diagram showing the effect of the amount of modified calcium carbonate used in Example 1 of the present invention and Comparative Example 2 on the performance of filled ABS;

[0080] In the figure: 1-weightless mixer for modification; 101-hollow interlayer; 102-stirring teeth; 103-flying knife; 104-transmission shaft; 105-additive addition port; 106-raw material addition port; 2-discharging motor of weightless mixer for modification; 3-weightless mixer for cooling; 4-discharging motor of cooling weightless mixer; 5-weightlessness metering system; 501-power device; 502-hopper; 503-screw; 504-barrel; 505-feeding barrel; 6-metering pump metering system 1; 601-infusion tube 1; 602-metering pump 1; 603-liquid storage tank 1 ;604-heating tube;605-filter;606-nozzle rod;607-nozzle;608-liquid outlet;7-metering pump metering system two;701-infusion tube two;702-metering pump two;703-liquid storage tank two;8-metering pump metering system three;801-infusion tube three;802-metering pump three;803-liquid storage tank three;9-metering pump metering system four;901-infusion tube four;902-metering pump four;903-liquid storage tank four;10-metering pump metering system five;1001-infusion tube five;1002-metering pump five;1003-liquid storage tank five. DETAILED DESCRIPTION

[0081] The present invention is further described below in conjunction with the accompanying drawings and examples. In the following detailed description, certain exemplary embodiments of the present invention are described only by way of illustration. Needless to say, those of ordinary skill in the art will recognize that the described embodiments may be modified in various ways without departing from the spirit and scope of the present invention. Therefore, the drawings and description are illustrative in nature and are not intended to limit the scope of protection of the claims.

[0082] The highly filled modified calcium carbonate powder for improving the performance of ABS comprises the following components in proportion by weight: 100 parts of calcium carbonate powder, 0.5-0.7 parts of stearic acid, 0.5-0.8 parts of long-chain silane coupling agent, 0.6-1.0 parts of aluminate coupling agent, 0.3-0.5 parts of titanate coupling agent, 1.0-1.3 parts of modifier, and 0.3-0.5 parts of dispersant. The particle size of the calcium carbonate powder tested by Malvern particle size tester is D 50 ≦1.54μm, D 97 Heavy calcium carbonate powder ≦9.38μm.

[0083] In this embodiment, the raw material ore for preparing the heavy calcium carbonate powder is large calcite or small calcite, which is obtained by grinding and classifying the ore using a vertical mill; 1 to 1.5‰ of a grinding aid needs to be added during grinding; the grinding aid is one of sodium dodecyl sulfate, sodium hexametaphosphate, and sodium polystyrene sulfonate.

[0084] The preparation of the heavy calcium carbonate powder comprises the following steps:

[0085] SP A1 , cleaning: use tap water or clean water to clean the ore to remove the mud and humus adhering to the surface of the ore.

[0086] SP A2 3. Sorting: sorting the cleaned ore to remove the miscellaneous ores that affect the white hue.

[0087] SP A3 , first breaking, using a jaw crusher to break the ore into small pieces of ore.

[0088] SP A4 2. Secondary crushing: use jaw crusher to crush small pieces of ore into crushed ore with a maximum size not exceeding 30mm.

[0089] SP A5 , dilution, take distilled water with a mass of 15 to 25 times that of the grinding aid, add the distilled water to the grinding aid to dilute it, and then pour it into a liquid storage tank equipped with a metering pump, the liquid inlet of the metering pump is connected to the lower part of the liquid storage tank and close to its bottom, the liquid outlet of the metering pump is connected to an infusion tube, the infusion tube is connected to a nozzle rod, and a nozzle is installed on the nozzle rod.

[0090] SP A6 , spray, SP A4 The crushed ore obtained in the step is metered and transported to the vertical mill through a vibrating screen. During the transportation of the crushed ore, the diluted grinding aid is sprayed onto the surface of the crushed ore through a metering pump according to a set mass ratio with the crushed ore.

[0091] SP A7 , grinding, adjusting the process parameters of the vertical mill for grinding, the vertical mill outputs the calcium carbonate powder mixed with large particles of calcium carbonate into the classifier for classification, the large particles of calcium carbonate are returned to the vertical mill after classification to continue to participate in grinding, the calcium carbonate powder enters the collector for classification, and the collector parameters are adjusted to separate the coarse powder and the fine powder, and the particle size of the fine powder is D 50 ≦1.54μm, D 97 Calcium carbonate powder ≦9.38μm.

[0092] The grinding aid mechanism of the grinding aid is as follows: when the ore is ground, the grinding aid is adsorbed on the new surface of the stone, reducing the external stress required for crack expansion when the particles are broken, and promoting the expansion of the cracks. As the specific surface area and specific surface energy of the particles increase, the bond force between adjacent atoms breaks, and this bond force is naturally activated on the new surface formed after the ore is crushed. Due to the initial stage of crushing, the new surface tends to be generated along the original fine cracks or strength weakened parts inside the particles, and the bond force on the new surface is relatively small. When the crushing time is extended and the particle size is reduced, the unsaturation degree on the new surface will gradually increase. The increase in its surface energy and the mechanical activation effect make the added grinding aid spontaneously perform physical adsorption and chemical adsorption on the new surface, among which the chemical adsorption effect is more prominent. Since the adsorption of these molecules reduces the surface energy and generates steric hindrance, it can prevent the aggregation and recrystallization between particles, and play a role in dispersion and grinding.

[0093] The reasons for diluting the grinding aid with distilled water before use are: ① Since the amount of grinding aid used is only 1-1.5‰ of the mass of the ore, the grinding aid can be amplified with the help of distilled water, which helps to achieve accurate metered addition of the grinding aid; ② Diluting the grinding aid with distilled water can avoid the adverse effects of metal ions or other ions contained in water bodies such as tap water on the effectiveness of the grinding aid.

[0094] The long-chain silane coupling agent described in this embodiment is one of alkoxy-terminated polydimethylsiloxane, 1,3-bis[3-(1-methoxy-2-hydroxypropoxy)propyl]-terminated polysiloxane, and octadecyltrimethoxysilane;

[0095] The structural formula of the alkoxy-terminated polydimethylsiloxane is:

[0096]

[0097] Where a = 0 or 1, R 1 , R 2 is methyl or ethyl, and n is 20 to 300;

[0098] The structural formula of the 1,3-bis[3-(1-methoxy-2-hydroxypropoxy)propyl]-terminated polysiloxane is:

[0099]

[0100] n is 10 to 100;

[0101] The structural formula of the octadecyltrimethoxysilane is,

[0102]

[0103] The aluminate coupling agent is one of isopropyl distearoyl aluminate, phosphate acyloxy isooctyl aluminate, and anti-settling aluminate. The titanate coupling agent is one of isopropyl tris (dioctyl phosphate acyloxy) titanate and bis (dioctyl pyrophosphate) ethylene titanate.

[0104] There are two groups with different properties in the molecular structure of the long-chain silane coupling agent, the aluminate coupling agent, and the titanate coupling agent. One of the groups can react chemically with the polymer material or have good compatibility or entanglement with each other; the other group can form a chemical bond with the inorganic material or filler, which can improve the adhesion of the interface between the two materials and significantly improve the performance of the filled or enhanced polymer material.

[0105] The long-chain silane coupling agent selected by the present invention contains a hydrolyzable short-chain alkoxy group (-OR) and / or hydroxyl group (-OH) in its structure. The short-chain alkoxy group (-OR) contained in both the aluminate coupling agent and the titanate coupling agent can be hydrolyzed into a hydroxyl group (-OH) under the influence of the bound water of the calcium carbonate powder itself under the action of high temperature and stirring shear force, and react with the hydroxyl group (-OH) on the surface of the calcium carbonate powder to form a strong bond. The long-chain alkyl group in the stearic acid added at the same time is a lipophilic group, and the carboxyl group (-COOH) group contained in it is a hydrophilic group, which can generate a hydrogen bond with the hydroxyl group (-OH) on the surface of the calcium carbonate powder. When conditions are met, the carboxyl group (-COOH) can react with the hydroxyl group (-OH) on the surface of the calcium carbonate powder to form an ester group (-COO).

[0106] The long-chain silane coupling agent contains long chains formed by polydimethylsiloxane with n polymerization degrees, which are entangled with the matrix material used during processing, thereby improving the performance of the composite material and increasing the bonding strength; the other end of the aluminate coupling agent is an organic long-chain group, which can be chemically cross-linked and physically entangled with the polymer molecular chain, thereby significantly improving the processing performance and physical and mechanical properties of the product, and forming an organic monolayer to cover the surface of the calcium carbonate; in addition to the functional area coupled with the calcium carbonate powder, the titanate coupling agent also has functional area ① ester transfer and cross-linking groups, functional area ② groups connected to the titanium center, and the groups in this part can produce different application functions depending on the different connecting groups, functional area ③ long chain entanglement groups, functional area ④ reaction groups, and functional area ⑤ non-hydrolyzable group quantity. The role of the non-hydrolyzable group is to strengthen the entanglement, and the large number of carbon atoms can drastically change the surface energy and significantly reduce the viscosity of the system. Siloxane, especially polysiloxane, also has a low surface energy and can efficiently migrate to the ABS surface to form a lubricating layer rich in polysiloxane, thereby improving the fluidity of the filled ABS.

[0107] The B phase in ABS plastic is butadiene, which has the following two main characteristics: ① The double bonds in butadiene are easily broken due to high temperature and shear force during processing; ② The interaction between the B phase butadiene in ABS and the inorganic rigid particle calcium carbonate is a restrictive factor affecting the large-scale filling of ABS plastic. The combination of stearic acid with long-chain silane coupling agent, aluminate coupling agent and titanate coupling agent can, on the one hand, combine the titanate coupling agent with the chain break through chemical reaction when the butadiene chain breaks, thereby delaying the continued occurrence of chain break; on the other hand, the organic monolayer formed by the combination of stearic acid and aluminate coupling agent avoids direct contact between butadiene and the calcium carbonate rigid particle powder; on the third hand, the long chain of the long-chain silane coupling agent, aluminate coupling agent, titanate coupling agent and stearic acid is entangled with the ABS plastic molecular chain, and the long chain of the long-chain silane coupling agent, aluminate coupling agent, titanate coupling agent and stearic acid is entangled with each other, which is beneficial to improve the mechanical properties of ABS plastic materials. Through the composite use of the above three types of coupling agents and the combination with stearic acid, the functions of coupling, grafting / cross-linking, entanglement, lubrication, etc. are realized, and together constitute the modified CaCO 3 Performance guarantee when powder is filled with large amounts of ABS plastic material.

[0108] The modifier is ethyl levulinate glycidyl ketal, C 21 One of the diglycidyl dicarboxylate. The structural formula of the ethyl ester of glycidyl levulinate is:

[0109]

[0110] The C 21 The structural formula of diglycidyl dicarboxylate is:

[0111]

[0112] The mechanism of action of the modifier: the ethyl acetal of levulinic acid glycidyl ester or C 21 Diglycidyl dicarboxylate is an epoxy compound with a long chain structure. On the one hand, during the processing, its long chain structure is entangled with the ABS plastic molecular chain and the long chain silane coupling agent, the aluminate coupling agent, the titanate coupling agent, and the long chain of stearic acid, so that when the filled ABS material breaks, a large amount of energy is consumed for disentanglement, which plays a toughening role and can make up for the influence of the rigid calcium carbonate particles on the ABS plastic substrate. On the other hand, the highly active epoxy groups contained in it It has the ability to open the ring under processing conditions and combine with the chain breaking of B phase butadiene in the ABS plastic processing process, which reduces the risk of degradation in the ABS plastic processing process, thereby extending the molecular chain structure of the ABS plastic and improving the performance of the modified calcium carbonate filled ABS plastic; thirdly, it contains highly active epoxy groups The ring opening under processing conditions can chemically react with a very small amount of hydroxyl groups (-OH) on the surface of the calcium carbonate powder that may not be modified by the stearic acid, the long-chain silane coupling agent, the aluminate coupling agent, and the titanate coupling agent, thereby contributing to the improvement of the performance of the blending system.

[0113] The dispersant is a hyperdispersant, including one of a pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type hyperdispersant, a styrene-butyl acrylate-2-acrylamide-2-methylpropane sulfonic acid ternary copolymer, and a sulfonate type hyperdispersant;

[0114] The structural formula of the pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type hyperdispersant is

[0115] Where n:m:f=7:36:1;

[0116] The structural formula of the 2-acrylamide-2-methylpropanesulfonic acid-styrene-butyl acrylate terpolymer is:

[0117]

[0118] Where x:y:z=1:1:0.5;

[0119] The structural formula of the sulfonate type hyperdispersant is:

[0120]

[0121] Among them, a:b:c=1:0.5:1, and n is 8 to 10.

[0122] Dispersing mechanism of the dispersant: The dispersants are all hyperdispersants. The structure of hyperdispersants consists of two parts: anchoring groups and solvating groups. The anchoring groups are mainly combined with the surface of powder particles through ionic bonds, hydrogen bonds and van der Waals forces, adsorbed on the surface of particles, and form an adsorption layer around the particles, which is not easy to desorb; the solvating groups contain solvating chains to form a coating layer on the surface of particles. According to the three-dimensional (spatial) stability mechanism, when two particles adsorbed with hyperdispersant molecules are close to each other and the distance between them is less than 2 times the thickness of the adsorption layer, the steric hindrance generated by the extended solvating chains causes the particles to bounce off and prevent them from agglomerating.

[0123] The present embodiment also relates to a method for preparing the above-mentioned highly filled modified calcium carbonate powder for improving ABS performance, which is prepared by combining an auxiliary metering system group and a weightless mixing unit, wherein the auxiliary metering system group includes five metering pump metering systems and a loss-in-weight scale metering system; the weightless mixing unit includes a weightless mixer 1 for modification and a weightless mixer 3 for cooling.

[0124] like Figures 1 to 6 As shown, a discharge port is provided in the middle of the bottom of the weightless mixer 1 for modification, and a discharge motor 2 for the weightless mixer for modification is installed below the discharge port. The weightless mixer for cooling is connected to the discharge motor 2 for modification. A discharge port is provided in the middle of the bottom of the weightless mixer for cooling, and a discharge motor 4 for the cooling weightless mixer is installed below the discharge port.

[0125] The weightlessness weighing system 5 is installed above the modified zero-gravity mixer 1, and the weightlessness weighing system 5 includes a barrel 504, a hopper 502 is installed above the barrel 504, a blanking barrel 505 is installed at the discharge end of the barrel 504, a screw 503 is installed in the barrel 504, one end of the screw 503 extends to the outside of the feed end of the barrel 504, and the end of the screw 503 extending to the outside of the barrel 504 is connected to a power device 501.

[0126] The modified zero-gravity mixer 1 is sequentially connected to five metering pump metering systems, namely metering pump metering system 1 6, metering pump metering system 2 7, metering pump metering system 3 8, metering pump metering system 4 9 and metering pump metering system 5 10. Among them, the metering pump metering system 1 6 includes a liquid storage tank 1 603 with a heating function, the liquid outlet 608 of the liquid storage tank 1 603 is connected to the liquid inlet of the metering pump 1 602, and the liquid outlet of the metering pump 1 602 is connected to the infusion tube 1 601, such as Figure 5 As shown, the other end of the infusion tube 601 is installed with a nozzle rod 606, and the end of the nozzle rod 606 is installed with a nozzle 607. Figure 6 As shown, the nozzle 607 is provided with a number of spray holes. Figure 4 As shown, a heating tube 604 is installed in the liquid storage tank 1 603, and a filter screen 605 is installed on the side close to the liquid outlet 608, and the filter screen 605 is a stainless steel screen with a mesh size of 40 to 60.

[0127] The metering pump metering system 2 7 includes a liquid storage tank 2 703 with a heating function, the liquid outlet of the liquid storage tank 2 703 is connected to the liquid inlet of the metering pump 2 702, the metering pump 2 702 is connected to the infusion tube 2 701, the internal structure of the liquid storage tank 2 703 and its nozzle rod and nozzle are consistent with the structure of the metering pump metering system 1 6; the metering pump metering system 3 8 includes a liquid storage tank 3 803 with a heating function, the liquid outlet of the liquid storage tank 3 803 is connected to the liquid inlet of the metering pump 3 802, the metering pump 3 802 is connected to the infusion tube 3 801, the internal structure of the liquid storage tank 3 803 and its nozzle rod and nozzle are consistent with the structure of the metering pump metering system 1 6; the metering The metering pump metering system 49 includes a liquid storage tank 4903 with a heating function, the liquid outlet of the liquid storage tank 4903 is connected to the liquid inlet of the metering pump 4902, the metering pump 4902 is connected to the infusion tube 4901, the internal structure of the liquid storage tank 4903 and its nozzle rod and nozzle are consistent with the structure of the metering pump metering system 16; the metering pump metering system 510 includes a liquid storage tank 51003 with a heating function, the liquid outlet of the liquid storage tank 51003 is connected to the liquid inlet of the metering pump 51002, the metering pump 51002 is connected to the infusion tube 51001, the internal structure of the liquid storage tank 51003 and its nozzle rod and nozzle are consistent with the structure of the metering pump metering system 16.

[0128] like Figure 3 As shown, the modified weightless mixer 1 includes a shell, a chamber is arranged in the shell, the lower part of the chamber is an "ω"-shaped structure, and the upper part is a rectangular parallelepiped structure, two transmission shafts 104 are installed in parallel in the "ω"-shaped structure of the chamber, one end of each transmission shaft 104 is rotatably installed on the shell of the chamber, and is limited to the outside of the shell, and the other end extends to the outside of the shell and is connected to a power device through a chain drive, and a stirring tooth group is evenly installed on each of the transmission shafts 104, and the stirring tooth group is composed of four groups of mutually perpendicular stirring teeth 102, and the stirring teeth 102 are arranged at an angle of 45° with the corresponding transmission shaft 104, and the inner wall of the chamber is located below each of the transmission shafts 104. A flying knife 103 is installed; the shell is provided with a hollow interlayer 101, and the hollow interlayer 101 is connected to an external heat transfer oil heating system, and discharge ports are correspondingly arranged directly below the "ω" structure of the chamber, and a discharge motor 2 of a weightless mixer for modification is installed on the discharge port; a raw material addition port 106 is opened in the middle of the top of the weightless mixer 1 for modification, and an auxiliary agent addition port 105 is opened on one side of the raw material addition port 106, and the nozzle rods of the metering pump metering system 1 6, the metering pump metering system 2 7, the metering pump metering system 3 8, the metering pump metering system 4 9, and the metering pump metering system 5 10, and the blanking barrel 505 on the loss-in-weight scale metering system 5 are installed on the auxiliary agent addition port 105.

[0129] The structure of the cooling weightless mixer 3 is similar to that of the modifying weightless mixer 1. In the structure of the cooling weightless mixer 3, the top of the cooling weightless mixer 3 does not have the auxiliary agent addition port 105 opened on the modifying weightless mixer 1, and the remaining structure is consistent with the structure of the modifying weightless mixer 1. The hollow interlayer of the cooling weightless mixer 3 is connected to an external water cooling system. The raw material addition port opened on the top of the cooling weightless mixer 3 is connected to the discharge port of the modifying weightless mixer 1. The thermal oil heating system and the water cooling system are well known to ordinary technicians in this technical field and will not be described in detail here; the existence of the flying knife 103 can disrupt the running trajectory of the mixed material driven by the rotation of the stirring teeth 102, which is conducive to more complete mixing of the mixed material.

[0130] Therefore: the preparation method of this embodiment includes the following steps:

[0131] SP B1 1. Heat the weightless mixer 1 for modification, set the heating temperature to 85-90° C., and keep the temperature constant for 30 minutes after the heating reaches the set temperature. 2. Pass cooling water through the weightless mixer 3 for cooling.

[0132] SP B2 , putting stearic acid into the first metering pump metering system, that is, putting it into the liquid storage tank 603 of the metering pump metering system 6 for heating, and the heating temperature is controlled at 75-85°C; putting the long-chain silane coupling agent into the second metering pump metering system, that is, putting it into the liquid storage tank 2703 of the metering pump metering system 27 for heating, and the heating temperature is controlled at 65-75°C; putting the aluminate coupling agent into the third metering pump metering system, that is, putting it into the liquid storage tank 3803 of the metering pump metering system 38 for heating and melting, and the heating temperature is controlled at 85-95°C; putting the titanate coupling agent into the fourth metering pump metering system, that is, putting it into the liquid storage tank 4903 of the metering pump metering system 49 for heating, and the heating temperature is controlled at 50-60°C; putting the modifier into the fifth metering pump metering system, that is, putting it into the liquid storage tank 51003 of the metering pump metering system 5 for heating, and the heating temperature is controlled at 60-70°C.

[0133] SP B3 , placing the dispersant into the hopper 502 of the loss-in-weight measuring system 5 .

[0134] The above steps can be completed during the heating waiting process of the weightless mixer 1 for modification.

[0135] SP B4After the weightless mixer 1 for modification is heated to a constant temperature for 30 minutes, the weightless mixer 1 for modification is started to mix the step SP A7 The prepared calcium carbonate powder is metered into the weightless mixer 1 for modification. The amount of calcium carbonate powder added shall not exceed 2 / 3 of the volume of the weightless mixer 1 for modification. The speed of the weightless mixer 1 for modification is controlled at 50-70 rad / min.

[0136] SP B5 , start the power device of the loss-in-weight weighing system 5, measure the dispersant in the hopper 502 according to the mass ratio matching the mass ratio of calcium carbonate added to the modified zero-gravity mixer 1, and evenly add it into the modified zero-gravity mixer 1, and control the adding time to 60 to 75 seconds.

[0137] SP B6 1. When the temperature of the calcium carbonate powder in the modified zero-gravity mixer 1 reaches 85°C, start the metering pump 602 on the metering pump metering system 6 containing the stearic acid, and spray the heated molten stearic acid evenly onto the calcium carbonate powder in the modified zero-gravity mixer 1 according to the ratio, and the spraying time is controlled to be 30 to 45 seconds. 1 to 2 minutes after the spraying is completed, start the metering pump 702 on the metering pump metering system 7 containing the long-chain silane coupling agent, and spray the heated long-chain silane coupling agent evenly onto the calcium carbonate powder in the modified zero-gravity mixer 1 according to the ratio, and the spraying time is controlled to be 45 to 60 seconds. 1 to 2 minutes after the spraying is completed, start the metering pump 3802 on the metering pump metering system 38 in which the aluminate coupling agent is placed, and spray the heated molten aluminate coupling agent evenly onto the calcium carbonate powder in the modified weightless mixer 1 according to the ratio, and the spraying time is controlled to be 45 to 60 seconds. 1 to 2 minutes after the spraying is completed, start the metering pump 4902 on the metering pump metering system 49 in which the titanate coupling agent is placed, and spray the heated titanate coupling agent evenly onto the calcium carbonate powder in the modified weightless mixer 1 according to the ratio, and the spraying time is controlled to be 30 to 45 seconds. After spraying, stir and mix for 15 to 20 minutes.

[0138] SP B7 2. Start the metering pump 5 1002 on the metering pump metering system 5 10 containing the modifier. The viscosity of the modifier becomes thinner after being heated. Spray the modifier evenly onto the calcium carbonate powder in the weightless mixer 1 for modification according to the proportion. The spraying time is controlled to be 30 to 45 seconds. Continue stirring and mixing for 3 to 5 minutes.

[0139] SP B8, start the discharging motor 2 of the weightless mixer for modification, put the mixed materials into the weightless mixer for cooling 3 for stirring and cooling, and control the stirring speed to 50-70 rad / min.

[0140] SP B9 After the material is cooled to room temperature, the cooling weightless mixer discharge motor 4 is turned on to discharge the material and package it into finished products.

[0141] The purpose of sequentially adding the stearic acid, the long-chain silane coupling agent, the aluminate coupling agent and the titanate coupling agent and the short time difference between the additions is, on the one hand, to effectively prevent the mutual interference of the additives in the adding process; on the other hand, the short time difference is to ensure that the stearic acid, the long-chain silane coupling agent, the aluminate coupling agent and the titanate coupling agent are absorbed by the calcium carbonate without affecting each other, and to ensure that they compete with each other to combine with the hydroxyl group (-OH) on the surface of the calcium carbonate.

[0142] About the embodiment description:

[0143] ①Use D 50 1.10μm, D 97 5.83μm 3000 mesh powder, D 50 1.30μm, D 97 7.98μm 2700 mesh powder and D 50 1.46μm, D 97 Take 8.71μm 2500 mesh powder as an example;

[0144] ② Using different grinding aids, namely sodium dodecyl sulfate, sodium hexametaphosphate or sodium polystyrene sulfonate, under the premise of equal dosage, the particle size and whiteness of the calcium carbonate powder ground with the same fineness do not change much, and the specific test data are shown in Table 1. For simplicity, all the following embodiments are taken as an example of using sodium dodecyl sulfate added with 1.5‰ of the mass of calcium carbonate ore as a grinding aid.

[0145] Table 1 Effect of different grinding aids on powder particle size and blue light whiteness of calcium carbonate ore with a mass of 1.5‰

[0146]

[0147]

[0148] ③ The structural formula of the alkoxy-terminated polydimethylsiloxane used in the embodiment is,

[0149]

[0150] Among them, a is selected as 1, R 1 and R2 Select methyl for both and select 200 for n.

[0151] The structural formula of the 1,3-bis[3-(1-methoxy-2-hydroxypropoxy)propyl]-terminated polysiloxane used is:

[0152]

[0153] Among them, n is selected as 80.

[0154] ④ The modifier used in the embodiment is ethyl levulinate glycidyl ketal, and the structural formula is,

[0155]

[0156] Example 1

[0157] D 50 1.10μm, D 97 100 parts of calcium carbonate powder with a diameter of 5.83 μm, 0.7 parts of stearic acid, 0.8 parts of alkoxy-terminated polydimethylsiloxane, 1.0 parts of isopropyl distearoyloxyaluminate, 0.5 parts of isopropyl tri(dioctylphosphoyl)titanate, 1.3 parts of ethyl levulinic acid epoxyglycerol monoester ketal, and 0.5 parts of pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type hyperdispersant.

[0158] The obtained modified calcium carbonate powder was labeled as AII-1.

[0159] Prepare 5 groups of ABS plastics, each group uses 100 parts of general-grade ABS plastics, and add 5 parts, 10 parts, 20 parts, 30 parts, and 40 parts of modified calcium carbonate powder respectively and mix them, and mark them as AII-1-5, AII-1-10, AII-1-20, AII-1-30, and AII-1-40 respectively.

[0160] The mixed material is granulated at a granulation temperature of 180-230°C, dried in an oven at 75-85°C for 2h, and injection molded for testing at an injection molding temperature of 195-225°C.

[0161] Example 2

[0162] D 50 1.10μm, D 97 100 parts of calcium carbonate powder with a diameter of 5.83 μm, 0.5 parts of stearic acid, 0.5 parts of alkoxy-terminated polydimethylsiloxane, 0.6 parts of isopropyl distearoyloxyaluminate, 0.3 parts of isopropyl tri(dioctylphosphoyl)titanate, 1.0 parts of ethyl levulinic acid epoxyglycerol monoester ketal, and 0.3 parts of pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type hyperdispersant.

[0163] The obtained modified calcium carbonate powder was labeled as AII-2.

[0164] Use 100 parts of general-grade ABS plastic, add 30 parts of modified calcium carbonate powder and mix, and mark it as AII-2-30.

[0165] The mixture was granulated, injection molded and tested according to the conditions of Example 1.

[0166] Example 3

[0167] D 50 1.10μm, D 97 100 parts of calcium carbonate powder with a diameter of 5.83 μm, 0.6 parts of stearic acid, 0.7 parts of alkoxy-terminated polydimethylsiloxane, 0.8 parts of isopropyl distearoyloxyaluminate, 0.4 parts of isopropyl tri(dioctylphosphoyl)titanate, 1.15 parts of ethyl levulinic acid epoxyglycerol monoester ketal, and 0.4 parts of pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type hyperdispersant.

[0168] The obtained modified calcium carbonate powder was labeled as AII-3.

[0169] Use 100 parts of general-grade ABS plastic, add 30 parts of modified calcium carbonate powder and mix, and mark it as AII-3-30.

[0170] The mixed material was granulated, injection molded and tested according to the conditions of Example 1.

[0171] Example 4

[0172] D 50 1.10μm, D 97 100 parts of calcium carbonate powder with a diameter of 5.83 μm, 0.5 parts of stearic acid, 0.5 parts of alkoxy-terminated polydimethylsiloxane, 1.0 parts of isopropyl distearoyloxyaluminate, 0.5 parts of isopropyl tri(dioctylphosphoyloxy)titanate, 1.3 parts of ethyl levulinic acid epoxyglycerol monoester ketal, and 0.5 parts of pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type hyperdispersant.

[0173] The obtained modified calcium carbonate powder was labeled as AII-4.

[0174] Use 100 parts of general-grade ABS plastic, add 30 parts of modified calcium carbonate powder and mix, and mark it as AII-4-30.

[0175] The mixed material was granulated, injection molded and tested according to the conditions of Example 1.

[0176] Example 5

[0177] D50 1.10μm, D 97 100 parts of calcium carbonate powder with a diameter of 5.83 μm, 0.5 parts of stearic acid, 0.5 parts of alkoxy-terminated polydimethylsiloxane, 0.6 parts of isopropyl distearoyloxyaluminate, 0.5 parts of isopropyl tri(dioctylphosphoyl)titanate, 1.3 parts of ethyl levulinic acid epoxyglycerol monoester ketal, and 0.5 parts of pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type hyperdispersant.

[0178] The obtained modified calcium carbonate powder was labeled as AII-5.

[0179] Use 100 parts of general-grade ABS plastic, add 30 parts of modified calcium carbonate powder and mix, and mark it as AII-5-30.

[0180] The mixed material was granulated, injection molded and tested according to the conditions of Example 1.

[0181] Example 6

[0182] D 50 1.10μm, D 97 100 parts of calcium carbonate powder with a diameter of 5.83 μm, 0.5 parts of stearic acid, 0.5 parts of alkoxy-terminated polydimethylsiloxane, 0.6 parts of isopropyl distearoyloxyaluminate, 0.5 parts of isopropyl tri(dioctylphosphoyl)titanate, 1.0 parts of ethyl levulinic acid epoxyglycerol monoester ketal, and 0.5 parts of pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type hyperdispersant.

[0183] The obtained modified calcium carbonate powder was labeled as AII-6.

[0184] Use 100 parts of general-grade ABS plastic, add 30 parts of modified calcium carbonate powder and mix, and mark it as AII-6-30.

[0185] The mixed material was granulated, injection molded and tested according to the conditions of Example 1.

[0186] Example 7

[0187] D 50 1.10μm, D 97 100 parts of calcium carbonate powder with a diameter of 5.83 μm, 0.5 parts of stearic acid, 0.5 parts of alkoxy-terminated polydimethylsiloxane, 0.8 parts of isopropyl distearoyloxyaluminate, 0.5 parts of isopropyl tri(dioctylphosphoyl)titanate, 1.3 parts of ethyl levulinic acid epoxyglycerol monoester ketal, and 0.5 parts of pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type hyperdispersant.

[0188] The obtained modified calcium carbonate powder was labeled as AII-7.

[0189] Use 100 parts of general-grade ABS plastic, add 30 parts of modified calcium carbonate powder and mix, and mark it as AII-7-30.

[0190] The mixed material was granulated, injection molded and tested according to the conditions of Example 1.

[0191] Example 8

[0192] D 50 1.10μm, D 97 100 parts of calcium carbonate powder with a diameter of 5.83 μm, 0.5 parts of stearic acid, 0.5 parts of alkoxy-terminated polydimethylsiloxane, 0.8 parts of isopropyl distearoyloxyaluminate, 0.4 parts of isopropyl tri(dioctylphosphoyl)titanate, 1.3 parts of ethyl levulinic acid epoxyglycerol monoester ketal, and 0.5 parts of pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type hyperdispersant.

[0193] The obtained modified calcium carbonate powder was labeled as AII-8.

[0194] Use 100 parts of general-grade ABS plastic, add 30 parts of modified calcium carbonate powder and mix, and mark it as AII-8-30.

[0195] The mixed material was granulated, injection molded and tested according to the conditions of Example 1.

[0196] Example 9

[0197] D 50 1.10μm, D 97 100 parts of calcium carbonate powder with a diameter of 5.83 μm, 0.5 parts of stearic acid, 0.5 parts of alkoxy-terminated polydimethylsiloxane, 1.0 parts of isopropyl distearoyloxyaluminate, 0.4 parts of isopropyl tri(dioctylphosphoyloxy)titanate, 1.3 parts of ethyl levulinic acid epoxyglycerol monoester ketal, and 0.5 parts of pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type hyperdispersant.

[0198] The obtained modified calcium carbonate powder was labeled as AII-9.

[0199] Use 100 parts of general-grade ABS plastic, add 30 parts of modified calcium carbonate powder and mix, and mark it as AII-9-30.

[0200] The mixed material was granulated, injection molded and tested according to the conditions of Example 1.

[0201] Example 10

[0202] D 50 1.10μm, D 97100 parts of calcium carbonate powder with a diameter of 5.83 μm, 0.7 parts of stearic acid, 0.5 parts of alkoxy-terminated polydimethylsiloxane, 1.0 parts of isopropyl distearoyloxyaluminate, 0.5 parts of isopropyl tri(dioctylphosphoyloxy)titanate, 1.3 parts of ethyl levulinic acid epoxyglycerol monoester ketal, and 0.5 parts of pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type hyperdispersant.

[0203] The obtained modified calcium carbonate powder was labeled as AII-10.

[0204] Use 100 parts of general-grade ABS plastic, add 30 parts of modified calcium carbonate powder and mix, and mark it as AII-10-30.

[0205] The mixed material was granulated, injection molded and tested according to the conditions of Example 1.

[0206] Embodiment 11

[0207] D 50 D 50 =1.30μm, D 97 = 7.98 μm calcium carbonate powder 100 parts, stearic acid 0.7 parts, alkoxy-terminated polydimethylsiloxane 0.8, isopropyl distearoyloxyaluminate 1.0 parts, isopropyl tri(dioctylphosphoacyloxy)titanate 0.5 parts, levulinic acid epoxyglycerol monoester ethyl ketal 1.3 parts, pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type hyperdispersant 0.5 parts.

[0208] The obtained modified calcium carbonate powder was labeled as AII-11.

[0209] 100 parts of general-grade ABS plastic were used, and 30 parts of modified calcium carbonate powder were added and mixed, and the mixture was marked as AII-11-30 respectively.

[0210] The mixed material is granulated at a temperature of 180-230°C, and then injection molded for sample testing at a temperature of 195-225°C.

[0211] Example 12

[0212] D 50 D 50 =1.46μm, D 97 = 100 parts of calcium carbonate powder with a diameter of 8.71 μm, 0.7 parts of stearic acid, 0.8 parts of alkoxy-terminated polydimethylsiloxane, 1.0 parts of isopropyl distearoyloxyaluminate, 0.5 parts of isopropyl tri(dioctylphosphoacyloxy)titanate, 1.3 parts of ethyl levulinic acid epoxyglycerol monoester ketal, and 0.5 parts of pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type super dispersant.

[0213] The obtained modified calcium carbonate powder was labeled as AII-12.

[0214] 100 parts of general-grade ABS plastic were used, and 30 parts of modified calcium carbonate powder were added and mixed, and the mixture was marked as AII-12-30 respectively.

[0215] The mixed material is granulated at a temperature of 180-230°C, and then injection molded for sample testing at a temperature of 195-225°C.

[0216] Example 13

[0217] D 50 1.10μm, D 97 100 parts of calcium carbonate powder with a diameter of 5.83 μm, 0.7 parts of stearic acid, 0.8 parts of 1,3-bis[3-(1-methoxy-2-hydroxypropoxy)propyl] end-capped polysiloxane, 1.0 parts of isopropyl distearoyloxyaluminate, 0.5 parts of isopropyl tri(dioctylphosphoyloxy)titanate, 1.3 parts of ethyl levulinic acid epoxyglycerol monoester ketal, and 0.5 parts of pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type hyperdispersant.

[0218] The obtained modified calcium carbonate powder was labeled as BII-1.

[0219] Use 100 parts of general-grade ABS plastic, add 30 parts of modified calcium carbonate powder and mix, and mark it as BII-1-30.

[0220] The mixed material was granulated, injection molded and tested according to the conditions of Example 1.

[0221] Embodiment 14

[0222] D 50 1.10μm, D 97 100 parts of calcium carbonate powder with a diameter of 5.83 μm, 0.7 parts of stearic acid, 0.8 parts of 1,3-bis[3-(1-methoxy-2-hydroxypropoxy)propyl] end-capped polysiloxane, 1.0 parts of phosphate acyloxyisooctanol aluminate, 0.5 parts of isopropyl tri(dioctyl phosphate acyloxy) titanate, 1.3 parts of ethyl levulinic acid glycidyl monoester ketal, and 0.5 parts of pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type hyperdispersant.

[0223] The obtained modified calcium carbonate powder was labeled as BPI-1.

[0224] Use 100 parts of general-purpose ABS plastic, add 30 parts of modified calcium carbonate powder and mix, and mark it as BPI-1-30.

[0225] The mixed material was granulated, injection molded and tested according to the conditions of Example 1.

[0226] Embodiment 15

[0227] D 50 1.10μm, D 97 100 parts of calcium carbonate powder with a diameter of 5.83 μm, 0.7 parts of stearic acid, 0.8 parts of 1,3-bis[3-(1-methoxy-2-hydroxypropoxy)propyl] end-capped polysiloxane, 1.0 parts of anti-settling aluminate, 0.5 parts of isopropyl tri(dioctylphosphoyl)titanate, 1.3 parts of ethyl levulinic acid glycidyl monoester ketal, and 0.5 parts of pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type hyperdispersant.

[0228] The obtained modified calcium carbonate powder was labeled as BAI-1.

[0229] Use 100 parts of general-grade ABS plastic, add 30 parts of modified calcium carbonate powder and mix, and mark it as BAI-1-30.

[0230] The mixed material was granulated, injection molded and tested according to the conditions of Example 1.

[0231] Example 16

[0232] D 50 1.10μm, D 97 100 parts of calcium carbonate powder with a diameter of 5.83 μm, 0.7 parts of stearic acid, 0.8 parts of 1,3-bis[3-(1-methoxy-2-hydroxypropoxy)propyl] end-capped polysiloxane, 1.0 parts of isopropyl distearoyloxyaluminate, 0.5 parts of bis(dioctylpyrophosphate)ethylene titanate, 1.3 parts of ethyl levulinic acid glycidyl monoester ketal, and 0.5 parts of pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type hyperdispersant.

[0233] The obtained modified calcium carbonate powder was labeled as BIB-1.

[0234] Use 100 parts of general-grade ABS plastic, add 30 parts of modified calcium carbonate powder and mix, and mark it as BIB-1-30.

[0235] The mixed material was granulated, injection molded and tested according to the conditions of Example 1.

[0236] Embodiment 17

[0237] D 50 1.10μm, D 97100 parts of calcium carbonate powder with a diameter of 5.83 μm, 0.7 parts of stearic acid, 0.8 parts of 1,3-bis[3-(1-methoxy-2-hydroxypropoxy)propyl]-terminated polysiloxane, 1.0 parts of isopropyl distearyloxyaluminate, 0.5 parts of isopropyl tri(dioctylphosphoyloxy)titanate, C 21 1.3 parts of dicarboxylic acid diglycidyl ester, 0.5 parts of pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type super dispersant.

[0238] The obtained modified calcium carbonate powder was labeled as BII-2.

[0239] Use 100 parts of general-grade ABS plastic, add 30 parts of modified calcium carbonate powder and mix, and mark it as BII-2-30.

[0240] The mixed material was granulated, injection molded and tested according to the conditions of Example 1.

[0241] Embodiment 18

[0242] D 50 1.10μm, D 97 100 parts of calcium carbonate powder with a diameter of 5.83 μm, 0.7 parts of stearic acid, 0.8 parts of 1,3-bis[3-(1-methoxy-2-hydroxypropoxy)propyl] end-capped polysiloxane, 1.0 parts of isopropyl distearyloxyaluminate, 0.5 parts of isopropyl tri(dioctylphosphoyloxy)titanate, 1.3 parts of ethyl levulinate glycidyl monoester ketal, and 0.5 parts of styrene-butyl acrylate-2-acrylamide-2-methylpropanesulfonic acid terpolymer.

[0243] The obtained modified calcium carbonate powder was labeled as BII-3.

[0244] Use 100 parts of general-grade ABS plastic, add 30 parts of modified calcium carbonate powder and mix, and mark it as BII-3-30.

[0245] The mixed material was granulated, injection molded and tested according to the conditions of Example 1.

[0246] Embodiment 19

[0247] D 50 1.10μm, D 97 100 parts of calcium carbonate powder with a diameter of 5.83 μm, 0.7 parts of stearic acid, 0.8 parts of 1,3-bis[3-(1-methoxy-2-hydroxypropoxy)propyl] end-capped polysiloxane, 1.0 parts of isopropyl distearoyloxyaluminate, 0.5 parts of isopropyl tri(dioctylphosphoyloxy)titanate, 1.3 parts of ethyl levulinate glycidyl ketal, and 0.5 parts of sulfonate-type hyperdispersant.

[0248] The obtained modified calcium carbonate powder was labeled as BII-4.

[0249] Use 100 parts of general-purpose ABS plastic, add 30 parts of modified calcium carbonate powder and mix, and mark it as BII-4-30.

[0250] The mixed material was granulated, injection molded and tested according to the conditions of Example 1.

[0251] Embodiment 20

[0252] D 50 1.10μm, D 97 100 parts of calcium carbonate powder with a diameter of 5.83 μm, 0.7 parts of stearic acid, 0.8 parts of octadecyltrimethoxysilane, 1.0 parts of isopropyl distearoyloxyaluminate, 0.5 parts of isopropyl tri(dioctylphosphoyl)titanate, 1.3 parts of ethyl levulinic acid epoxyglycerol monoester ketal, and 0.5 parts of pentadecylphenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type hyperdispersant.

[0253] The obtained modified calcium carbonate powder was labeled as OII-1.

[0254] Use 100 parts of general-grade ABS plastic, add 30 parts of modified calcium carbonate powder and mix, and mark it as OII-1-30.

[0255] The mixed material was granulated, injection molded and tested according to the conditions of Example 1.

[0256] Comparative Example 1

[0257] General-purpose ABS plastic was injection molded and tested according to the conditions of Example 1.

[0258] Comparative Example 2

[0259] Prepare 5 groups of ABS plastics, each group uses 100 parts of general-grade ABS plastics, and adds 5 parts, 10 parts, 20 parts, 30 parts, and 40 parts of calcium carbonate powder respectively. The calcium carbonate powder is D activated with 1.9% stearic acid. 50 1.10μm, D 97 The calcium carbonate powder with a diameter of 5.83 μm was granulated, injection molded and tested according to the conditions of Example 1.

[0260] They are marked as Comparative Example 2-5, Comparative Example 2-10, Comparative Example 2-20, Comparative Example 2-30, and Comparative Example 2-40 respectively.

[0261] Comparative Example 3

[0262] 100 parts of ABS plastic, add 30 parts of calcium carbonate powder, the calcium carbonate powder is activated by 1.9% silane coupling agent KH550 50 1.10μm, D97 The calcium carbonate powder with a diameter of 5.83 μm was granulated, injection molded and tested according to the conditions of Example 1.

[0263] Marked as Comparative Example 3-30

[0264] Comparative Example 4

[0265] 100 parts of ABS plastic, add 30 parts of calcium carbonate powder, the calcium carbonate powder is activated by 1.9% isopropyl distearoyloxyaluminate D 50 1.10μm, D 97 The calcium carbonate powder with a diameter of 5.83 μm was granulated, injection molded and tested according to the conditions of Example 1.

[0266] Marked as Comparative Example 4-30

[0267] Comparative Example 5

[0268] 100 parts of ABS plastic, add 30 parts of calcium carbonate powder, the calcium carbonate powder is activated by 1.9% isopropyl tri (dioctyl phosphate acyloxy) titanate D 50 1.10μm, D 97 The calcium carbonate powder with a diameter of 5.83 μm was granulated, injection molded and tested according to the conditions of Example 1.

[0269] Marked as Comparative Example 5-30

[0270] The modified calcium carbonate powders in Examples 1 to 20 were tested for activation degree and oil absorption value according to GB / T 19281-2014 "Analysis Method for Calcium Carbonate", and the blue light whiteness test was performed according to GB / T 23774-2009 "General Method for Determination of Whiteness of Inorganic Chemical Products". The test data are shown in Table 2.

[0271] Table 2 Test data of modified calcium carbonate powder

[0272]

[0273] For all embodiments and comparative examples, the tensile strength was tested according to GB / T 1040.2-2022 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics", the notched impact strength was tested according to GB / T 1043.1-2018 "Determination of impact properties of simple supported beams of plastics Part 1: Non-instrumented impact test", the melt index was tested according to GB / T 3682.1-2018 "Determination of melt mass flow rate (MFR) and melt volume flow rate (MVR) of thermoplastics Part 1: Standard method", the heat deformation temperature was tested according to GB / T 1634.2-2004 "Determination of deflection temperature of plastics under load Part 2: Plastics, hard rubber and long fiber reinforced composites", the flexural strength was tested according to GB / T 9341-2008 "Determination of flexural properties of plastics", and the flexural strength was tested according to JIS Z 8741:1997 "Surface gloss - Measurement method" tests the surface gloss. The test data are shown in Tables 3 to 6.

[0274] Table 3 Test data of Examples 1 to 6

[0275]

[0276] Table 4 Test data of Examples 7 to 15

[0277]

[0278] Table 5 Test data of Example 16 to Example 20 and Comparative Example 1 to Part of Comparative Example 2

[0279]

[0280] Table 6 Test data of some comparative examples 2 to 5

[0281]

[0282] By comparing the test data in Table 2, it can be found that the particle size D of the modified calcium carbonate powder 50 =1.10μm, D 97 =5.83μm blue light whiteness decreased from 95.1% to 94.5%, a decrease of 6.3‰, and the particle size D 50 =1.30μm, D 97 =7.98μm blue light whiteness decreased from 94.7% to 94.4%, a decrease of 3.2‰, and the particle size D 50 =1.46μm, D 97=8.71μm blue light whiteness decreased from 94.2% to 93.7%, a decrease of 5.3‰; the lowest activation degree was as high as 98.5%, and the oil absorption values ​​decreased from 32g / 100g, 31g / 100g, 25.5g / 100g to no more than 17g / 100g, 12g / 100g, 10g / 100g, respectively, with an obvious decrease. After comparison, it can be seen that the blue light whiteness of modified calcium carbonate powder is only reduced by 6.3‰ compared with that of calcium carbonate powder, so it still has a considerable whiteness. At the same time, modified calcium carbonate powder also has the characteristics of high activation degree and low oil absorption value.

[0283] By comparing the test data in Tables 3 to 6, it can be seen that the modified calcium carbonate powder filled ABS plastic blending system material in Examples 1 to 20 contributes significantly to the improvement of ABS material performance. The performance of ABS filled with modified calcium carbonate powder in Examples 1 (excluding AII-1-5 and AII-1-10) to 20 far exceeds the performance of ABS filled with modified calcium carbonate in Comparative Examples 2 to 5, and is higher than the performance of ABS raw material in Comparative Example 1 (except AII-1-40). The reason why the tensile strength, bending strength and heat deformation temperature of AII-1-5 in Example 1 are slightly reduced and lower than the ABS raw material in Comparative Example 1 and the tensile strength and bending strength of AII-1-10 in Example 1 are lower than those of Comparative Example 2-10 in Comparative Example 2 is that the combined use of the stearic acid, the long-chain silane coupling agent, the aluminate coupling agent, the titanate coupling agent and the modifier has a greater effect on the flexibility of the blending system than the rigidity effect brought by calcium carbonate.

[0284] The addition of inorganic rigid particles of calcium carbonate increases the heat distortion temperature significantly, so the change in heat distortion temperature will not be described in the following description.

[0285] In Example 1 (AII-1-5 to AII-1-40), the amount of modified calcium carbonate increased from 5 parts to 40 parts. Only when the amount of modified calcium carbonate was 5 parts, the comprehensive performance of the filled ABS decreased slightly, but the impact strength and melt index were still increased to a certain extent compared with the ABS raw material in Comparative Example 1. When the amount of modified calcium carbonate reached 10 parts, all the properties of the filled ABS were higher than those of the ABS raw material in Comparative Example 1. When the amount of modified calcium carbonate reached 40 parts, the comprehensive performance of the filled ABS was still equivalent to that of the ABS raw material in Comparative Example 1, and when the amount of modified calcium carbonate was 20 parts, the various properties of the filled ABS reached the highest, among which the impact strength and melt index were increased by 58.2% and 51.8% respectively; Comparative Example 2 (Comparative Example 2-5 to Comparative Example 2-40), a single additive modified calcium carbonate was used to fill ABS, and the amount of modified calcium carbonate was increased from 5 parts to 40 parts, and the amount of modified calcium carbonate was When the amount of modified calcium carbonate reaches 10 parts, the comprehensive performance of ABS filled reaches the highest, among which the impact strength, which is the largest improvement compared with the ABS raw material in Comparative Example 1, is only increased by 24.5%. When the amount of modified calcium carbonate reaches 20 parts, the performance is reduced to a level lower than that of the ABS raw material in Comparative Example 1, among which the impact strength decreases the most, reaching 16.4%. When the amount of modified calcium carbonate reaches 30 parts, all properties are greatly reduced compared with the ABS raw material in Comparative Example 1. The amounts of modified calcium carbonate are 30 parts and 40 parts respectively. Compared with the ABS raw material in Comparative Example 1, the tensile strength decreases by 25% and 42.0%, the impact strength decreases by 50.9% and 65.5%, the melt index decreases by 17.1% and 25.6%, and the flexural strength decreases by 14.3% and 32.2%. Please refer to the performance change trend of ABS filled with multiple additives modified calcium carbonate and single additive modified calcium carbonate in Example 1 and Comparative Example 2 for details, that is, Figure 7 and Figure 8 In the figure, the starting point of each performance change is the ABS raw material performance of Comparative Example 1.

[0286] Compared with Example 2 (stearic acid + long-chain silane coupling agent + aluminate coupling agent + titanate coupling agent) with the same amount of powder processing additives, Comparative Example 2 (stearic acid), Comparative Example 3 (long-chain silane coupling agent), Comparative Example 4 (aluminate coupling agent), and Comparative Example 5 (titanate coupling agent), especially Example 2 (AII-2-30) and Comparative Example 2-30 of Comparative Example 2, Comparative Example 3 (Comparative Example 3-30), Comparative Example 4 (Comparative Example 4-30), and Comparative Example 5 (Comparative Example 5-30), Example 2 (AII-2-30) filled with ABS has a very prominent performance improvement effect.

[0287] By comparing the surface glossiness of Examples 1 to 20 with Comparative Examples 1 to 5, it can be seen that the modified calcium carbonate of the present invention has the effect of improving the surface glossiness.

[0288] This is due to the composite use of the stearic acid, the long-chain silane coupling agent, the aluminate coupling agent and the titanate coupling agent, the highly active carboxyl (-COOH) and alkoxy (-OR) groups contained therein and the hydroxyl (-OH) on the surface of the calcium carbonate to form hydrogen bonds or chemical reactions. At the same time, the addition of the long-chain epoxy structure modifier, the highly active epoxy groups contained therein It has the ability to open the ring and break the chain of B phase butadiene in the ABS plastic processing process. At the same time, in the blending system, the stearic acid, the long-chain silane coupling agent, the aluminate coupling agent, the titanate coupling agent, the modifier and the ABS are intertwined, and the long chains of the long-chain silane coupling agent, the aluminate coupling agent, the titanate coupling agent and the stearic acid are intertwined, resulting in a more complete structure and increased energy required for disentanglement. On the other hand, the composite use of the stearic acid and the aluminate coupling agent forms an organic monolayer on the surface of calcium carbonate, avoiding the contact between calcium carbonate and B phase butadiene in ABS. The siloxane of the long-chain silane coupling agent, especially the polysiloxane, has a low surface energy and can efficiently migrate to the surface of ABS during the application process, thereby forming a lubricating layer rich in polysiloxane. In addition, the use of an efficient hyperdispersant makes the filled ABS have high mechanical and thermodynamic properties, high fluidity and high surface gloss.

[0289] When the comprehensive performance of Examples 1 to 20 is the highest, the filling amount of modified calcium carbonate is 20 parts (AII-1-20). The amount of modified calcium carbonate to achieve the best comprehensive performance is 20 parts higher than the amount of 10 parts in Comparative Example 2-10 in Comparative Example 2 in Table 5, and the performance is better than Comparative Example 2-10 in Comparative Example 2. The optimal amount of modified calcium carbonate is also much higher than that of "Dong Jiajia. Nano CaCO 3 Modification and its application in plastics [D]. Hefei University of Technology, 2021.5.", "Zhou Zhicun, Mo Bing, Chen Yuanyuan, et al. Research on the blending modification of ultrafine calcium carbonate and ABS plastics [J]. Modern Salt Chemical Industry, 2020, (6): 57-58.", "Lei Zubi, Wang Fei, Ma Mei. Research on the influence of fillers on the properties of ABS plastics [J]. Aging and Application of Synthetic Materials, 2024, 53 (1): 47-49." and other public literature usage. It can be seen that the modified calcium carbonate powder material of the present invention not only makes a great contribution to the improvement of the comprehensive performance of calcium carbonate-filled ABS plastics, but also the use of a larger amount of modified calcium carbonate filling also provides feasibility for further reducing the cost of ABS plastic materials.

[0290] The description of the present invention is given for the purpose of illustration and description, and is not intended to be exhaustive or to limit the invention to the disclosed form. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for particular uses.

Claims

1. Highly filled modified calcium carbonate powder for improving ABS performance, characterized by: The composition comprises the following components in proportion by weight: 100 parts of calcium carbonate powder, 0.5-0.7 parts of stearic acid, 0.5-0.8 parts of long-chain silane coupling agent, 0.6-1.0 parts of aluminate coupling agent, 0.3-0.5 parts of titanate coupling agent, 1.0-1.3 parts of modifier, and 0.3-0.5 parts of dispersant.

2. The highly filled modified calcium carbonate powder for improving ABS performance as claimed in claim 1, characterized in that: The particle size of the calcium carbonate powder tested by Malvern particle size tester is D 50 ≦1.54μm, D 97 Heavy calcium carbonate powder ≦9.38μm.

3. The highly filled modified calcium carbonate powder for improving ABS performance as claimed in claim 2, characterized in that: The raw material ore for preparing the heavy calcium carbonate powder is large calcite or small calcite, which is obtained by grinding with a vertical mill and then classifying; When the ore is ground, 1 to 1.5‰ of grinding aid needs to be added; The grinding aid is one of sodium dodecyl sulfonate, sodium hexametaphosphate and sodium polystyrene sulfonate; The preparation of the heavy calcium carbonate powder comprises the following steps: SP A1 , washing, using tap water or clean water to wash the ore to remove the sand and humus adhering to the surface of the ore; SP A2 3. Sorting: sorting the cleaned ore to remove the miscellaneous colored ore that affects the white hue; SP A3 First, crushing the ore into small pieces by using a jaw crusher; SP A4 Secondary crushing: jaw crusher is used to crush small pieces of ore into crushed ore with a maximum size not exceeding 30mm; SP A5 , dilution, taking distilled water of 15 to 25 times the mass of the grinding aid, adding the distilled water to the grinding aid to dilute it, and then pouring it into a liquid storage tank equipped with a metering pump, the liquid inlet of the metering pump is connected to the lower part of the liquid storage tank and close to the bottom thereof, the liquid outlet of the metering pump is connected to an infusion tube, the infusion tube is connected to a nozzle rod, and the nozzle rod is equipped with a nozzle; SP A6 , spray, SP A4 The crushed ore obtained in the step is metered and transported to the vertical mill by a vibrating screen. During the transportation of the crushed ore, the diluted grinding aid is sprayed onto the surface of the crushed ore by a metering pump according to a set mass ratio with the crushed ore; SP A7 , grinding, adjusting the process parameters of the vertical mill for grinding, the vertical mill outputs the calcium carbonate powder mixed with large particles of calcium carbonate into the classifier for classification, the large particles of calcium carbonate are returned to the vertical mill after classification to continue to participate in grinding, the calcium carbonate powder enters the collector for classification, and the collector parameters are adjusted to separate the coarse powder and the fine powder, and the particle size of the fine powder is D 50 ≦1.54μm, D 97 Calcium carbonate powder ≦9.38μm.

4. The highly filled modified calcium carbonate powder for improving ABS performance as claimed in claim 1, characterized in that: The long-chain silane coupling agent is one of alkoxy-terminated polydimethylsiloxane, 1,3-bis[3-(1-methoxy-2-hydroxypropoxy)propyl]-terminated polysiloxane, and octadecyltrimethoxysilane; The structural formula of the alkoxy-terminated polydimethylsiloxane is: Where a = 0 or 1, R 1 , R 2 is methyl or ethyl, and n is 20 to 300; The structural formula of the 1,3-bis[3-(1-methoxy-2-hydroxypropoxy)propyl]-terminated polysiloxane is: n is 10 to 100; The structural formula of the octadecyltrimethoxysilane is, 5. The highly filled modified calcium carbonate powder for improving ABS performance as claimed in claim 1, characterized in that: The aluminate coupling agent is one of isopropyl distearoyloxy aluminate, phosphate acyloxy isooctyl aluminate, and anti-settling aluminate.

6. The highly filled modified calcium carbonate powder for improving ABS performance as claimed in claim 1, characterized in that: The titanate coupling agent is one of isopropyl tri(dioctyl phosphate acyloxy) titanate and bis(dioctyl pyrophosphate) ethylene titanate.

7. The highly filled modified calcium carbonate powder for improving ABS performance as claimed in claim 1, characterized in that: The modifier is ethyl levulinate glycidyl ketal, C 21 One of the diglycidyl esters of dicarboxylic acids; The structural formula of the ethyl levulinate glycidyl ketal is: The C 21 The structural formula of diglycidyl dicarboxylate is:

8. The highly filled modified calcium carbonate powder for improving ABS performance as claimed in claim 1, characterized in that: The dispersant is a hyperdispersant, including one of a pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type hyperdispersant, a styrene-butyl acrylate-2-acrylamide-2-methylpropane sulfonic acid ternary copolymer, and a sulfonate type hyperdispersant; The structural formula of the pentadecyl phenyl acrylate-methacrylic acid-butyl acrylate ternary polyester type hyperdispersant is Where n:m:f=7:36:1; The structural formula of the 2-acrylamide-2-methylpropanesulfonic acid-styrene-butyl acrylate terpolymer is: Where x:y:z=1:1:0.5; The structural formula of the sulfonate type hyperdispersant is: Among them, a:b:c=1:0.5:1, and n is 8 to 10.

9. The method for preparing a highly filled modified calcium carbonate powder for improving ABS performance as claimed in claim 3, wherein the powder is prepared by combining an auxiliary metering system group and a zero-gravity mixer group, characterized in that :: The additive metering system group includes five metering pump metering systems and one loss-in-weight scale metering system; The zero-gravity mixer unit includes a zero-gravity mixer for modification and a zero-gravity mixer for cooling; The metering pump metering system comprises a liquid storage tank with a heating function, a metering pump connected to the liquid storage tank, a liquid infusion tube connected to the metering pump, a nozzle rod installed at the other end of the liquid infusion tube, and a nozzle installed at the end of the nozzle rod; The loss-in-weight weighing system comprises a barrel, a hopper is installed above the barrel, a blanking barrel is installed at the discharge end of the barrel, a screw is installed inside the barrel, one end of the screw extends to the outside of the feed end of the barrel, and the end of the screw extending to the outside of the barrel is connected to a power device; The modified zero-gravity mixer comprises a shell, a chamber is arranged in the shell, the lower part of the chamber is in an "ω"-shaped structure, and the upper part is in a rectangular parallelepiped structure, two transmission shafts are installed in parallel in the "ω"-shaped structure of the chamber, one end of each transmission shaft is rotatably installed on the shell, and is limited to the outside of the shell, and the other end extends to the outside of the shell and is connected to a power device through a chain drive, and stirring tooth groups are evenly installed on each of the transmission shafts, and the stirring tooth groups are respectively composed of four groups of mutually perpendicular stirring teeth, and the stirring teeth are arranged at an angle of 45° with the corresponding transmission shafts, and the inner wall of the chamber is located at each Flying knives are respectively installed below the transmission shaft; the shell is provided with a hollow interlayer, which is connected to an external heat transfer oil heating system, and discharge ports are respectively correspondingly arranged directly below the "ω" structure of the chamber, and a discharge motor of a weightless mixer for modification is installed on the discharge port; a raw material addition port is opened in the middle of the top of the weightless mixer for modification, and an auxiliary agent addition port is opened on one side of the raw material addition port, and the nozzle rod of the metering pump metering system and the blanking barrel of the weightlessness metering system are both installed on the auxiliary agent addition port; the hollow interlayer of the cooling weightless mixer is connected to a water cooling system.

10. The preparation method according to claim 9, characterized in that: The following steps are included: SP B1 , heating the modified weightless mixer, setting the heating temperature to 85-95° C., and maintaining the temperature for 30 minutes after the heating reaches the set temperature; passing cooling water through the cooling weightless mixer; SP B2 , placing stearic acid into the liquid storage tank of the first metering pump metering system and heating it to melt, and the heating temperature is controlled at 75-85°C; placing the long-chain silane coupling agent into the liquid storage tank of the second metering pump metering system and heating it, and the heating temperature is controlled at 65-75°C; placing the aluminate coupling agent into the liquid storage tank of the third metering pump metering system and heating it to melt, and the heating temperature is controlled at 85-95°C; placing the titanate coupling agent into the liquid storage tank of the fourth metering pump metering system and heating it, and the heating temperature is controlled at 50-60°C; placing the modifier into the liquid storage tank of the fifth metering pump metering system and heating it, and the heating temperature is controlled at 60-70°C; SP B3 , placing the dispersant into the hopper of the loss-in-weight measuring system; SP B4 , start the weightless mixer for modification, and mix the A7 The prepared calcium carbonate powder is metered into the weightless mixer for modification, the amount of calcium carbonate powder added shall not exceed 2 / 3 of the volume of the weightless mixer for modification, and the speed of the weightless mixer for modification is controlled at 50-70 rad / min; SP B5 , start the power device of the loss-in-weight weighing system, measure the dispersant in the hopper according to the mass ratio matching the mass ratio of calcium carbonate added to the modified zero-gravity mixer and evenly add it into the modified zero-gravity mixer, and control the adding time to 60 to 75 seconds; SP B6 2. When the temperature of the calcium carbonate powder mixed with the dispersant in the modified zero-gravity mixer reaches 85°C, start the metering pump on the metering system of the metering pump containing the stearic acid, and spray the heated molten stearic acid evenly onto the calcium carbonate powder in the modified zero-gravity mixer according to the ratio, and the spraying time is controlled to be 30 to 45 seconds. 1 to 2 minutes after the spraying is completed, start the metering pump on the metering system of the metering pump containing the long-chain silane coupling agent, and spray the heated long-chain silane coupling agent evenly onto the calcium carbonate powder in the modified zero-gravity mixer according to the ratio, and the spraying time is controlled to be 45 to 50 seconds. 60s, 1 to 2 minutes after the spraying is completed, the metering pump on the metering pump metering system with the aluminate coupling agent is started again, and the molten aluminate coupling agent is evenly sprayed onto the calcium carbonate powder in the modified zero-gravity mixer according to the ratio, and the spraying time is controlled to be 45 to 60s. 1 to 2 minutes after the spraying is completed, the metering pump on the metering pump metering system with the titanate coupling agent is started again, and the heated titanate coupling agent is evenly sprayed onto the calcium carbonate powder in the modified zero-gravity mixer according to the ratio, and the spraying time is controlled to be 30 to 45s. After the spraying is completed, stirring and mixing is performed for 15 to 20 minutes; SP B7 , start the metering pump on the metering pump metering system where the modifier is placed, spray the heated modifier evenly onto the calcium carbonate powder in the weightless mixer for modification according to the proportion, control the spraying time to 30 to 45 seconds, and continue stirring and mixing for 3 to 5 minutes; SP B8 , start the discharging motor of the weightless mixer for modification, put the mixed materials into the weightless mixer for cooling for stirring and cooling, and control the stirring speed to 50-70 rad / min; SP B9 After the material is cooled to room temperature, the discharging motor of the cooling zero-gravity mixer installed at the bottom of the cooling zero-gravity mixer is turned on to discharge the material and package it into a finished product.